2021
DOI: 10.1088/1755-1315/943/1/012012
|View full text |Cite
|
Sign up to set email alerts
|

Role of Eco-Friendly Bio-Based Graphene-Oil Nanofluids on Friction Reduction for Wind Turbine Application

Abstract: Sustainable energy such as wind turbine is known as a green technology that minimize the carbon emission into environment. However, unwanted friction and wear in journal bearing of a wind turbine’s gearbox leads to reduction of power efficiency and increase the reliance onto fossil-fuel powered electricity. Lubricating oils are used in journal bearing to provide the hydrodynamic lubrication film. However, commercially available lubricants are petroleum-based, which are non-replenishable and toxic. Thus, the bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
0
1
0
Order By: Relevance
“…This is further evidence that solid lubricants still have a lot of room for development. In order to decrease lubricant contamination and toxicity, Ng et al [ 132 ] synthesized high oleic acid POME with graphene nanoparticles (GNP), multi-walled carbon nanotubes (MWCNT), and nano-structured graphite (NSG), respectively. Experiments showed that the graphene nanoparticles in high oleic acid had a significant reduction in friction and wear.…”
Section: Research On Bearings Lubrication Technology Of Wind Turbinementioning
confidence: 99%
“…This is further evidence that solid lubricants still have a lot of room for development. In order to decrease lubricant contamination and toxicity, Ng et al [ 132 ] synthesized high oleic acid POME with graphene nanoparticles (GNP), multi-walled carbon nanotubes (MWCNT), and nano-structured graphite (NSG), respectively. Experiments showed that the graphene nanoparticles in high oleic acid had a significant reduction in friction and wear.…”
Section: Research On Bearings Lubrication Technology Of Wind Turbinementioning
confidence: 99%
“…They concluded experimentally that the grease lubricant with a low base oil viscosity and high bleed rate had the best anti-wear characteristics. Ng et al [30] experimentally concluded that graphene nanoparticles in high oleic acid can significantly reduce the friction and wear of bearings. Saidi et al [31] prepared MoS 2 nanolubricant additives.…”
Section: Introductionmentioning
confidence: 99%